Boundary effects in a quasi-2d granular mono-layer - Smith, N. D. (2020)
This thesis primarily explores the behaviour of granular matter using a Quasi-2D experimental system developed during the course of this project. The aim of this project is to use granular materials as an analogue for molecular systems where the motion of individual particles cannot be directly studied. Initially the influence of the boundaries on density and the granular temperature of a horizontally orientated layer subjected to vertical vibration is investigated. A scaling for the radial density is identified which can collapse all data onto a single master curve. It is shown the granular material behaves most homogeneously when the density is high. The granular temperature is found to also vary radially depending on the system density. However the granular temperature did not collapse. It was found to exhibit a maximum temperature difference between the centre and edge for intermediate particle numbers when normalised by the max temperature. The source this of this maximum temperature difference was linked to the varying mean free path of the particles between the centre and edge. The variance of mean free path is attributed to the radial density variation. The radial profile shape is then investigated further through the use of a molecular dynamics simulation using the idea of a viscous drag to simulate particle-base friction. It is shown that the shape of the radial temperature and density profiles observed in the experimental system apparently depend on this drag term. Prompted by the discovery that high density systems have the most uniform temperature profile we investigated the possibility of experimentally studying a new concept, the orderphobic effect in 2d granular systems at high concentrations. The orderphobic effect predicts a force between ''impurities/intruders'' that are placed in a fluid capable of undergoing an order-disorder transition. However, the order-disorder transition must be a 1st order transition. Our results seem at odds with a few key studies which describe strategies to create a 1st order transition in 2d. None of the systems which were studied displayed first order behaviour. However, a potential route was identified using electrostatic charging. A fundamental study of the diffusive behaviour of particles on a rough surface was also conducted using high speed photography. This enabled the translational and rotational dynamics of a single ball to be tracked on different roughness surfaces. Two regimes were identified with intermittent and continuous dynamics respectively. The crossover in these regimes appear to depend on the surface roughness and particle size.